Vertex models: from cell mechanics to tissue morphogenesis. (19th May 2017) - Alt, Silvanus; Ganguly, Poulami; Salbreux, Guillaume
Abstract : Tissue morphogenesis requires the collective, coordinated motion and deformation of a large number of cells. Vertex model simulations for tissue mechanics have been developed to bridge the scales between force generation at the cellular level and tissue deformation and flows. We review here various formulations of vertex models that have been proposed for describing tissues in two and three dimensions. We discuss a generic formulation using a virtual work differential, and we review applications of vertex models to biological morphogenetic processes. We also highlight recent efforts to obtain continuum theories of tissue mechanics, which are effective, coarse-grained descriptions of vertex models. This article is part of the themed issue 'Systems morphodynamics: understanding the development of tissue hardware'.